Ultrafast Optical Nonlinearity of Liquid Phase Exfoliated Pdse2 Nanosheets. - Alotaibi, Manal Saleh (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
In recent years, the study of condensed matter and optical physics has resulted in increasing technological progress, and this study may be credited with a significant portion of current scientific research and technical innovation. Understanding the interaction of light and matter provides us with the capacity to harness the underlying physical processes, which we can then utilize to discover and comprehend more complicated behavior and phenomena. Meanwhile, a great deal of attention has been drawn to the characteristics of 2D nanomaterials such as graphene, TMDs (Transition Metal Dichalcogenides), et cetera. This class of 2D materials has the potential to make a significant impact on the area of valleytronics due to the extraordinary physical characteristics that they possess. Within the first Brillouin zone, this area is concerned with the regulation of the valley degree of freedom of materials that include numerous valleys. 2D nanomaterials have the potential to enhance the performance of the next generation of optoelectronics and nanoelectronics, as well as other devices. The nonlinear optical properties of these materials are of critical significance, since they may be utilised to infer the connection between macroscopic characteristics and the underlying quantum mechanical processes responsible for the nonlinear behavior. Two- harmonic generation, frequency difference generation, and saturable absorption are all examples of nonlinear optical processes. A combination of technical advancements, femtosecond laser pump-probe spectroscopy and Z- scan techniques, were used in this research to explore the ultrafast carrier dynamics of 2D PdSe2 as well as the nonlinear optical characteristics of the material. The subject of this project's investigation is the saturable absorption of PdSe2. This NLO characteristic is of particular importance due to the possible uses of saturable absorber mirrors in passively mode-locking lasers. A saturable absorber is a substance that transmits light at a rate that varies with the intensity of the light emitted. This has the effect of attenuating lower optical intensity and shortening the length of the pulses in the system. Given the large number of commercial applications for short pulse lasers in a range of fields, it is becoming more essential to choose an appropriate saturable absorber material. In this work, strong saturable absorption was found in 2D PdSe2 using Z-scans based on a femtosecond laser at a central wavelength of 800 nm. This NLO behaver was theoretically analysed in this thesis. 2D PdSe2was produced by liquid phase exfoliation and characterised using TEM, AFM, and so forth. The relaxation of excited carrier dynamics of P was also studied using an optical pump-probe method. In this work, strong saturable absorption was found in 2D Pdse2 using Z-scan measurements based on a femtosecond laser at a central wavelength of 800 nm. This NLO behaver was theoretically analysed in this thesis. 2D PdSe2 was produced by liquid phase exfoliation and characterised using TEM, AFM, and so forth. The relaxation of excited carrier dynamics of P was also studied based on an optical pump-probe method. In this work, strong saturable absorption was found in 2D PdSe2 using Z-scan based on a femtosecond laser at a central wavelength of 800 nm. This NLO behaver was theoretically analysed in this thesis 2D Pdse2 Was produced by liquid phase exfoliation and characterised using TEM, AFM, et cetera. The relaxation of excited carrier dynamics of P was also studied based on an optical pump-probe method. This could provide importance guidelines for practical applications of 2D PdSe2 as a saturable absorber in mode-locked lasers.
APPROVED